Apically positioned flap, free gingival graft and apically positioned flap with collagen matrix around dental implants: A randomized controlled trial. - Park, Jake. (2017)
Abstract: Background: Due to anatomical differences, soft tissue around dental implants may be more susceptible to inflammation and breakdown. Therefore, attached keratinized mucosa will be more critical for dental implant and its prosthesis. Studies have shown that free gingival graft, apically positioned flap and collagen matrix graft can be viable procedures to enhance soft tissue around dental implants. Aim: To evaluate patients' experience and effectiveness of different techniques to increase keratinized mucosa around implants. Materials and Methods: Subjects were randomly assigned and received one of the three procedures; apically positioned flap, free gingival graft or apically positioned flap with Mucograft. Surveys were filled out by the subjects regarding experience during and after the procedure. Keratinized mucosa was measured at 3 month follow-up visit. Results: Data for the primary outcome was collected from 28 subjects and 24 subjects presented for 3 month follow-up keratinized mucosa measurement. Mucograft group showed highest level of discomfort during healing between the 3 groups (P<0.05). Gain of keratinized mucosa measured at 3 months showed no statistically significant difference. Conclusion: Soft tissue augmentation utilizing Mucograft may cause more discomfort than other procedures during the healing period. All three procedures provide adequate amount of keratinized mucosa.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Periodontology.; Advisor: Yong Hur.; Committee: Paul Stark, Yumi Ogata, and James Hanley.; Keywords: Dentistry, and Medicine.